The effect of bakuchiol in the skin aging process: A systematic review - Priyanto, Olivia Jovina; Sugiyanto, Yosef Ferdinand Rahmat; Salim, Darryl Samuel (UI Scholars Hub, 2023)
Background: With aging, the skin gradually loses its structural and morphological coherence, decreasing its function. With aging and chronic ultraviolet (UV) exposure, the skin becomes thin and loses elasticity, and wrinkles, pigmentation, and texture irregularities appear. Today, people of all ages become interested in the cosmetic industry, aiming to make their skin appropriate to their age or look younger. Bakuchiol is a pure meroterpene phenol found mainly in the seeds of the Indian plant Psoralea corylifolia (babchi). It triggers antioxidant and anti-inflammatory activity and has anti-aging properties like retinol. The study aimed to know the effect of bakuchiol on the skin aging process. Methods: A systematic review of the literature was conducted. Data were collected and synthesized from online databases with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) protocol. Results: More than 125 articles were found, and six studies were selected according to this research. Of the six existing clinical trial studies, all showed that bakuchiol had a beneficial effect on reducing signs of skin aging. Conclusion: Bakuchiol has shown beneficial effects in preventing or reducing signs of skin aging, such as fine lines and wrinkles, loss of elasticity and firmness, dull skin, uneven hyperpigmentation, skin dryness, and texture irregularities, with minimal side effects.